Melacak Visi Hierofani di Balik Narasi Ngibau (Pemeliharaan Padi) Suku Dayak Peruan Kalimantan Barat - Berek, Yanuarius (Perspektif, 2021)
The focus of this article is to trace the hierophany vision behind the Ngibau (rice raising) narrative of the Dayak Peruan tribe of West Kalimantan. The narrative of raising rice of Dayak Peruan tribe, like many other narratives, is full of meaning. The depiction of raising rice is like a child who goes overseas by sailing the sea, facing tidal waves, until he returns to his homeland bringing with him the valuables stuffs that have been ordered by his parents to him. To open up the full of its meaning, the writer uses Mircea Eliade’s theory on hierophany of sacred realities.